Present-day variability and Holocene dynamics of permafrost-affected lakes in central Yakutia (Eastern Siberia) inferred from diatom records - Pestryakova, Luidmila A. (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.); Wetterich, Sebastian; Ulrich, Mathias (Quaternary Science Reviews, 2012)
Thermokarst lakes are assumed to develop cyclically, driven by processes that are triggered by climate and maintained by internal feedbacks that may trigger lake drainage. However, the duration of these cycles remains uncertain, as well as whether or not they affect the stabilization of lake ecosystems in permafrost regions over millennial time scales. Our research has combined investigations into modern lake-to-lake variability with a study of the long-term development of individual lakes. We have investigated the physico-chemical and diatom compositions of a set of 101 lakes with a variety of different origins in central Yakutia (Eastern Siberia), including thermokarst lakes, fluvial-erosion thermokarst lakes, fluvial-erosion lakes, and dune lakes. We found a significant relationship between lake genesis and the present-day variability in environmental and diatom characteristics, as revealed by multi-response permutation procedures, indicator species analyses, and redundancy analyses. Environmental parameters also exhibit a significant correlation with variations in the diatom data, for which they may have been to a substantial extent responsible. Mg and SO4 concentrations, together with pH and water depth, were identified as the most important parameters, influencing the variations in the diatom data almost as much as the entire environmental parameter set. We were therefore able to establish a robust Mg-diatom transfer function, which was then applied to three Holocene lake records. From these reconstructions, together with a general interpretation of the diatom record (including, e.g., the ratio between benthic/epiphytic and planktonic taxa), we have been able to infer that all three of these lakes show (1) a continuous record with no desiccation events, (2) high lake water-levels during the early Holocene, (3) centennial to millennial scale variability, and (4) high levels of variability during the early Holocene but rather stable conditions during the late Holocene (a feature that is also known from other ...